Does Diabetes have the potential to elevate the risk of Dementia? A Meta-Analysis - Dr. Duddela Varalakshmi; Mrs. Hannah Rajsekhar; Nerusu Mani Maheswari (The Bioscan, 2026)
Background:The relationship between diabetes and the risk of developing dementia remains inadequately understood. This study assesses the factors associated with the onset of dementia in individuals with diabetes, offering insights for the prevention of dementia among diabetic patients. Aim: To find out the factors associated with onset of Dementia in Diabetic individuals. Materials & Methods: This analysis employed databases including PubMed, Embase, Web of Science, and the Cochrane Library to examine literature from January 1, 2012, to March 31, 2024. Articles underwent a thorough evaluation based on defined inclusion and exclusion criteria. The Newcastle-Ottawa Scale (NOS) was employed to assess the quality of the studies. Results: The research examined 14 articles, and the meta-analysis indicates a significant correlation between diabetes and a heightened risk of dementia. A diabetes duration of under five years is associated with an increased risk of dementia. Conclusion: Diabetes significantly elevates the risk of dementia, especially in cases where the duration of diabetes is less than five years or when hypoglycaemia occurs.